Polimorfisme Gen VEGF-A (rs2010963) pada Turunan Pertama Penderita Penyakit Jantung Koroner (PJK) - Aurora Fajria Anwari; Novriantika Lestari; Marisadonna Asteria; Sipriyadi Sipriyadi; Ismir Fahri; Elvira Yunita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the VEGF-A gene polymorphism (rs2010963) in the first generation of patients with coronary heart disease (CHD) and non-CHD in Bengkulu City. The method used is molecular analysis of polymorphism through Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP). This type of research is descriptive observational with a cross-sectional research design. The results of this study indicate that the genotype frequency of the VEGF-A gene polymorphism (rs2010963) in the first generation of patients with CHD is genotype CC = 11 (52.4 %), GG = 7 (33.3%) and CG = 3 (14.3%). ). The distribution of the VEGF-A genotype (rs2010963) in the first non-CHD offspring, namely GG = 9 (42.9%), CC = 7 (33.3%) and GC = 5 (23.8%). The statistical analysis results showed that the p-value obtained was 0.460 for the VEGF-A gene polymorphism genotype (rs2010963) in the first CHD and Non-CHD derived samples. In conclusion, there was no significant difference in the VEGF-A gene polymorphism in the first generation of CHD and non-CHD groups in Bengkulu City. Keywords: PCR-RFLP, Coronary Heart Disease, Gene Polymorphism, VEGF-A